2018
DOI: 10.1371/journal.pgen.1007701
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor BRCA1-BARD1 complex localizes to the synaptonemal complex and regulates recombination under meiotic dysfunction in Caenorhabditis elegans

Abstract: Breast cancer susceptibility gene 1 (BRCA1) and binding partner BRCA1-associated RING domain protein 1 (BARD1) form an essential E3 ubiquitin ligase important for DNA damage repair and homologous recombination. The Caenorhabditis elegans orthologs, BRC-1 and BRD-1, also function in DNA damage repair, homologous recombination, as well as in meiosis. Using functional GFP fusions we show that in mitotically-dividing germ cells BRC-1 and BRD-1 are nucleoplasmic with enrichment at foci that partially overlap with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
88
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(108 citation statements)
references
References 117 publications
17
88
2
Order By: Relevance
“…Regarding DNA damage and repair, we observed an upregulation of phosphoS 1987 ATM and phosphoS 139 H2AX (histone variant, γ H2AX), reflecting increased levels of DNA damage in the MGT cells upon treatment (Figures 6a,b and 7a; Figure S6a, Supporting Information). This high proportion of DNA damage is associated to the downregulation of Rad51 (Figure 6a,b), which plays a major role in double‐strand break (DSB) repair by homologous recombination and in fork protection, and restart during replication stress, [ 48 ] raising the possibility that this downregulation is related to the increase of phosphoS 139 H2AX. Moreover, we observed a drastic downregulation of RRM2, a subunit of the ribonucleotide reductase required to maintain high levels of dNTPs, [ 23 ] with an upregulation of Histone‐H3 and H3K9me2 levels (Figure 6a–d; Figure S6b, Table S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding DNA damage and repair, we observed an upregulation of phosphoS 1987 ATM and phosphoS 139 H2AX (histone variant, γ H2AX), reflecting increased levels of DNA damage in the MGT cells upon treatment (Figures 6a,b and 7a; Figure S6a, Supporting Information). This high proportion of DNA damage is associated to the downregulation of Rad51 (Figure 6a,b), which plays a major role in double‐strand break (DSB) repair by homologous recombination and in fork protection, and restart during replication stress, [ 48 ] raising the possibility that this downregulation is related to the increase of phosphoS 139 H2AX. Moreover, we observed a drastic downregulation of RRM2, a subunit of the ribonucleotide reductase required to maintain high levels of dNTPs, [ 23 ] with an upregulation of Histone‐H3 and H3K9me2 levels (Figure 6a–d; Figure S6b, Table S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Further, we think it likely that the contributions of nucleoplasmic components in general have been underestimated. There is a growing recognition that proteins localized predominantly in the nucleoplasm can have a profound impact on chromosome structure (e.g., WAPL-1; Crawley et al 2016), that many chromosome-associated proteins also have substantial nucleoplasmic pools (e.g., Silva et al 2014;Janisiw et al 2018;Li et al 2018;Woglar and Villeneuve 2018), and that dynamic exchange can occur between protein pools in different subnuclear compartments (e.g., Pattabiraman et al 2017). Thus, we anticipate that future research will uncover roles for additional nucleoplasmic factors in promoting a successful outcome of the meiotic program.…”
Section: Rethinking the Neglected Nucleoplasmmentioning
confidence: 99%
“…Similarly, the model of Teuscher et al (2000) , based on data from a study on mouse and two studies on Drosophila , suggested that chromatid interference may play an important role in meiosis. Similarly, weak chromatid interference was deduced in maize, human oocytes, and Caenorhabditis elegans ( Hou et al , 2013 ; Li et al , 2015 ; Li et al , 2018 ). Our study offers clear and unambiguous evidence for a strong positive chromatid interference: the second crossover in an arm was formed more frequently between chromatids not involved in the first crossover ( Fig.…”
Section: Discussionmentioning
confidence: 85%